NUPR1 Interacts with p53, Transcriptionally Regulates p21 and Rescues Breast Epithelial Cells from Doxorubicin-Induced Genotoxic Stress - Clark, David W.; Mitra, Aparna; Fillmore, Rebecca A.; Jiang, Wen G.; Samant, Rajeev S.; Fodstad, Oystein; Shevde, Lalita A. (Current Cancer Drug Targets, 2008)
Nuclear protein 1 (NUPR1/com1/p8) has been shown to interact with transcriptional regulators such as p300, PTIP, estrogen receptor-β, and SMAD. NUPR1 also has been implicated in the regulation of cell cycle and apoptosis. An increase in NUPR1 expression has been seen with serum starvation and in response to compounds such as cycloheximide, ceramide, and staurosporine. There are several overtly conflicting reports about the exact role of NUPR1 in tumor biology. This work investigates the nature of the relationship between NUPR1 and the cdk-inhibitor p21 (Waf1/Cip1) expression. We show that the expression of resident and doxorubicin-induced p21 paralleled that of endogenous NUPR1 levels. NUPR1 formed a complex with p53 and p300 and bound the p21 promoter and transcriptionally upregulated p21 expression. Moreover, NUPR1 allowed cells to progress through cell cycle in presence of doxorubicin. Since NUPR1 upregulated p21, concomitant with phosphorylation of Rb and upregulation of the anti-apoptotic protein, Bcl-xL we propose that NUPR1 expression imparts a cell growth and survival advantage. Importantly, we also report that NUPR1 conferred resistance to two chemotherapeutic drugs, Taxol and doxorubicin.
Keywords: p53